Evaluation of the child-friendly school program (SRA) in Public Elementary Schools in East Kotawaringin Regency Using the CIPPO Model - Ananda Eka Mulya Hakimia; Bulkani Bulkani (Suluh: Jurnal Bimbingan dan Konseling, 2025)
The aim of this research is to evaluate the implementation of child-friendly school programs in public elementary schools in Mentawabaru Ketapang District, East Kotawaringin Regency. The research method used in this research is qualitative research with the CIPPO (Context, Input, Process, Product and Outcome) evaluation model. The results of this research showed that: (1) the results of an evaluation of the context in which the SRA Program was implemented were in accordance with the legal basis and in accordance with community needs; (2) the results of the input evaluation are the unavailability of KHA-certified teaching staff and the need for supporting facilities that comply with SRA regulations; (3) the results of the process evaluation aspect which is based on the linkage of the program with the internalization of child-friendly values ​​in the curriculum and all learning processes which are very good but there is still minimal stakeholder cooperation; (4) the results of the evaluation of the results during which the SRA program was implemented can be seen from the percentage reduction in violations committed by students by an average of 23.6%; (5) the results of the output aspect are that students have felt a positive impact on the formation of character or attitudes or behavior which then has an impact on the school environment and the community environment. It is hoped that the results of this research can become a reference for improvement and improvement for all parties involved in implementing the SRA program.